Genome-wide identification of the GLK transcription factor family in melon and its expression analysis under biotic and abiotic stresses - Zheng, Ling; Wang, Yuna; Lv, Fang; Han, Jianming (Frontiers in Plant Science, 2025)
This study systematically identifies and characterizes the GLK gene family in melon (Cucumis melo), identifying 49 GLK genes within the melon genome, which are subsequently named CmGLK1 to CmGLK49 based on their chromosomal locations. The CmGLK family members exhibit significant variation in physicochemical properties, including amino acid length, molecular weight, and isoelectric point. Phylogenetic analysis classified the CmGLK genes into six groups (I-VI), demonstrating a high degree of conservation of GLK genes across melon, cucumber, and watermelon. Motif and domain analyses indicate that all CmGLK family members possess the characteristic GLK transcription factor domain. Moreover, genes within the same phylogenetic group display similar protein motifs and gene structures, suggesting that these genes may have a common function in regulating plant growth and development. Chromosomal localization reveals that CmGLK genes are unevenly distributed across 12 chromosomes, with nine pairs of segmental duplications and one pair of tandem repeats, indicating that gene duplication likely plays a key role in the expansion of this gene family. Additionally, GLK homologs were identified between melon and Arabidopsis thaliana, Oryza sativa, Cucumis sativus, and Citrullus lanatus, with the highest homology found between melon and cucumber, as well as melon and watermelon. Cis-regulatory element analysis of CmGLK promoters reveals a high abundance of elements associated with light response, hormone regulation, and stress responses, suggesting that the CmGLK family may be involved in the regulation of melon growth, development, and environmental stress responses. Expression profiling shows that CmGLK genes are expressed in a tissue-specific manner, with the highest expression levels found in the root, stem, and leaf tissues. Further Quantitative fluorescence analysis reveals that several CmGLK family members exhibit significant expression changes under Fusarium wilt and drought stress, suggesting their potential involvement in melon’s stress response mechanisms. This study provides a comprehensive analysis of the structure, evolution, and stress-responsive expression of the CmGLK gene family. Our findings offer new insights into the potential molecular mechanisms of melon’s stress adaptation and highlight candidate CmGLK genes for future functional studies aimed at improving disease resistance.